Hidrólise enzimática do óleo de macaúba (Acrocomia aculeata) - Raspe, Djéssica Tatiane (2014)
Modification of vegetable oils and fats for biodiesel production have been widely studied, where the incentive to search for alternative raw materials for the production of this biofuel has been the focus of interest. Aiming to use an oleaginous without food purposes, with availability and low cost matrix, oil Macaúba (Acrocomia aculeata) has been reported, with its large production potential. In this context, the aim of this study was to investigate the production of free fatty acids (FFA) through the enzymatic hydrolysis process, the initial reaction hidroesterificação. Front to yield free fatty acids (FFAs) were evaluated different commercial enzymatic catalysts (Lipozyme® RM IM, Lipozyme® TL IM and Novozyme® 435), addition of sodium phosphate buffer at different pHs (5.7-8.0), salts (CuCl2, CaCl2, KCl, NH4Cl, NaCl, MgCl2), surfactants (Triton X-100, Tween 80) and organic (n-hexane, n-heptane, isopropanol, tert-butanol) solvent, as well as process variables: agitation (400-2000 rpm), temperature (30-60 °C), weight ratio of substrates (1:20-1:1 oil:water) and percentage of catalyst (1-20% by mass of oil). The results show that the addition of a buffer solution (pH 8.0) and organic solvent n-hexane contributed significantly to the increase in free fatty acids in the hydrolysis yield being obtained approximately 82% at 55 °C oil weight ratio: Buffer 1:2, 100% n-hexane solvent relative to the weight of oil and 400 rpm for 6 hours reaction, 15% Lipozyme® RM IM. The reaction conditions of the process were explored in the presence of n-hexane organic solvent by means of experimental design, in order to maximize the yield FFAs in the process, as well as obtaining the kinetics of production of FFAs. Given the variables, it can be seen that no increase in yields of FFA by increasing the weight ratio of oil:solvent n-hexane, temperature, buffer and percentage of catalyst variables that influence the process significantly. In reaction kinetics, about 88% free fatty acids were produced in reaction medium consisting of 70% buffer, 100% of n-hexane solvent and 15% of catalyst, reaction for 8 hours. The reuse of the enzyme catalyst has been reported before 20 reaction cycles, where it was detected decrease of approximately 50% of revenue in the initial FFA process.